Effect of Implantable Collamer Lens on Anterior Segment Measurement and Intraocular Lens Power Calculation Based on IOLMaster 700 and Sirius. (21st December 2021) - Chen, Xiaoyong; Zhang, Di; Liu, Ziyuan; Liu, Yinan; Cai, Hongyuan; Wu, Qianru; Zhang, Yu
Abstract : Purpose . To investigate the possible effect of an implantable collamer lens (ICL) on ocular biometrics and intraocular lens (IOL) power calculation. Methods . Ocular measurements were taken preoperatively and at the two-month follow-up using IOLMaster 700 and Sirius in 85 eyes (43 patients) who had previously undergone ICL surgery. IOL power was calculated using either IOLMaster 700 (Barrett Universal II formula) or Sirius (ray-tracing). All data were compared using the paired t -test. Results . The difference between preoperative and postoperative anterior chamber depth (ACD), lens thickness (LT), and keratometry on the steep axis (K2) measured by IOLMaster 700 was statistically significant ( p < 0.001). In 11 of 85 eyes, IOLMaster misjudged the anterior surface of the ICL as that of the lens, leading to an error in ACD and LT. There were no significant differences between preoperative and postoperative axial length (AL) ( p = 0.223), white to white (WTW) ( p = 0.100), keratometry on flat axis (K1) ( p = 0.117), or central corneal thickness (CCT) ( p = 0.648), measured using IOLMaster. The difference in IOL power calculated using the Barrett II formula was significant ( p = 0.013). Regression analysis showed that AL and K had the greatest influence on IOL calculation ( p < 0.001), and ACD and LT had less influence ( p = 0.002, p = 0.218, respectively). K1 and K2 were modified to exclude the influence of K2, and modified IOLs showed no difference between pre and postoperation ( p = 0.372). Preoperative and postoperative ACD measured using Sirius were significantly different ( p < 0.001); however, the IOL power calculated using ray-tracing technology showed no significant differences ( p > 0.05). Conclusions . The ocular biometric apparatus may misjudge the anterior surface of the lens, resulting in measurement errors of ACD and LT, which has little effect on the calculation of IOL power when using IOLMaster 700 (Barrett Universal II formula) and Sirius (ray-tracing).